2022
DOI: 10.3389/fsurg.2022.846470
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Serum CysC, IMA, and LP-PLA2 Levels With Type 2 Diabetes Mellitus Patients With Lower Extremity Atherosclerotic Occlusive Disease

Abstract: ObjectiveTo investigate the serum level of cystatin C (CysC), ischemia-modified albumin (IMA), and lipoprotein-associated phospholipase A2 (LP-PLA2) in patients with type 2 diabetes mellitus (T2DM) and with lower extremity atherosclerotic occlusive disease (LEASOD) and their correlation.MethodsFrom March 2017 to December 2019, 110 patients with T2DM with LEASOD, who were treated in our hospital, were selected as the observation group. One hundred ten healthy persons who received medical examination in our hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The inclusion criteria were as follows: Patients met the diagnostic guidelines for T2DM and lower extremity arteriosclerosis obliterans; Patients had a medical history of T2DM with symptoms such as limb pain, intermittent claudication or ischemic ulcer, and gangrene in the lower limbs, and LEASOD was confirmed through color Doppler ultrasound, CT angiography, and other imageological tests to detect the corresponding artery stenosis or occlusion, and all patients should have complete clinical data. 6 The exclusion criteria were included patients who had acute complications of T2DM, patients with hemorrhagic diseases or disorders of the coagulation system, patients with cerebrovascular diseases, patients with severe cardiopulmonary liver and kidney failure, patients with infectious or autoimmune diseases, fever or infection, current smokers, vaccination within 3 months, history of prior organ transplantation, steroid use, estrogen replacement, AIDS, on chronic anti-inflammatory use, chemotherapy within the prior year, acquired Immune Deficiency Syndrome or immunocompromised, hemochromatosis, diagnosed with cancers, or neurodegenerative disease. 6 The average age of these patients was 50.25 ± 6.16, with the majority being between 45 and 55 years old (age ranged from 41 to 59).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion criteria were as follows: Patients met the diagnostic guidelines for T2DM and lower extremity arteriosclerosis obliterans; Patients had a medical history of T2DM with symptoms such as limb pain, intermittent claudication or ischemic ulcer, and gangrene in the lower limbs, and LEASOD was confirmed through color Doppler ultrasound, CT angiography, and other imageological tests to detect the corresponding artery stenosis or occlusion, and all patients should have complete clinical data. 6 The exclusion criteria were included patients who had acute complications of T2DM, patients with hemorrhagic diseases or disorders of the coagulation system, patients with cerebrovascular diseases, patients with severe cardiopulmonary liver and kidney failure, patients with infectious or autoimmune diseases, fever or infection, current smokers, vaccination within 3 months, history of prior organ transplantation, steroid use, estrogen replacement, AIDS, on chronic anti-inflammatory use, chemotherapy within the prior year, acquired Immune Deficiency Syndrome or immunocompromised, hemochromatosis, diagnosed with cancers, or neurodegenerative disease. 6 The average age of these patients was 50.25 ± 6.16, with the majority being between 45 and 55 years old (age ranged from 41 to 59).…”
Section: Methodsmentioning
confidence: 99%
“… 6 The exclusion criteria were included patients who had acute complications of T2DM, patients with hemorrhagic diseases or disorders of the coagulation system, patients with cerebrovascular diseases, patients with severe cardiopulmonary liver and kidney failure, patients with infectious or autoimmune diseases, fever or infection, current smokers, vaccination within 3 months, history of prior organ transplantation, steroid use, estrogen replacement, AIDS, on chronic anti-inflammatory use, chemotherapy within the prior year, acquired Immune Deficiency Syndrome or immunocompromised, hemochromatosis, diagnosed with cancers, or neurodegenerative disease. 6 The average age of these patients was 50.25 ± 6.16, with the majority being between 45 and 55 years old (age ranged from 41 to 59). Demographic data and medication of the study population are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that Lp-PLA2 levels were elevated in individuals with type 2 diabetes and that Lp-PLA2 levels were higher in diabetic individuals with cognitive impairment compared to those without cognitive impairment ( Cai et al, 2017 ). Studies have reported the role of Lp-PLA2 in cognitive impairment-related diseases such as Alzheimer’s disease and diabetes ( Davidson et al, 2012 ; Feng et al, 2022 ). These results have shown elevated plasma levels of Lp-PLA2 in patients with these diseases, which are strongly associated with cognitive decline.…”
Section: Introductionmentioning
confidence: 99%